2013
DOI: 10.1002/qj.2081
|View full text |Cite
|
Sign up to set email alerts
|

Using an ultrahigh‐resolution regional climate model to predict local climatology

Abstract: Many applications of risk assessment and Environmental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Subkilometer-scale models are emerging from being run experimentally to actually aiding forecasts: for instance, the London and Weymouth 333-m models (Golding et al 2013;Wang et al 2013), model development for the High Definition Clouds and Precipitation for Climate Prediction project, and Environment Canada's highresolution model development for outdoor venues at the 2015 Toronto Pan-Am Games. We therefore require novel observational strategies and diagnostic tools for model evaluation.…”
Section: Is 200-m Resolution Good Enough?mentioning
confidence: 99%
“…Subkilometer-scale models are emerging from being run experimentally to actually aiding forecasts: for instance, the London and Weymouth 333-m models (Golding et al 2013;Wang et al 2013), model development for the High Definition Clouds and Precipitation for Climate Prediction project, and Environment Canada's highresolution model development for outdoor venues at the 2015 Toronto Pan-Am Games. We therefore require novel observational strategies and diagnostic tools for model evaluation.…”
Section: Is 200-m Resolution Good Enough?mentioning
confidence: 99%
“…Cholette et al (2015) have shown that with grid meshes of 1-3 km, the fifth-generation Canadian Regional Climate Model (CRCM5) showed a clear improvement in the simulation of wind channelling effect in the St. Lawrence River Valley located in Québec, Canada. The study of Wang et al (2013) revealed that high resolution improves local features such as sea breezes and funnelling winds in the Met Office United Model (MetUM) RCM. In the case of simulations over complex topography with the Weather Research and Forecasting (WRF) RCM version 3.0, Rasmussen et al (2011) have shown that spatial snowfall distribution is much more representative of observations with 2 km than 36 km grid-mesh simulations; they attributed this result to a more realistic vertical motion at higher resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Regional climate models (RCMs; e.g., Giorgi 1990) have been implemented over specific areas of interest with resolutions as high as 500 m (Wang et al 2013) compared to 50-300 km for a GCM. Typically, such studies run the RCM one or at most a handful of times.…”
mentioning
confidence: 99%